H-Cube: innovative Harumanis Perlis product / Rafidah Aida Ramli ... [et al.] - Ramli, Rafidah Aida; Azmi, Azila; Ahmad, Zamri; Abu, Nurul Nadia; Abdul Wahab, Mohd Faisal; Mohd Ariffin, Zianatul Ashikin; Othman, Hafizuddin (Universiti Teknologi MARA, Kedah, 2019)
Harumanis mangoes are one of the best mangoes in the world produced in the smallest state in the Northern tip of Malaysia - Perlis. Whilst most of Harumanis mangoes are exported to Japan, Singapore and the rest of the world each year, major customers of this authentic mangoes still the fellow Malaysians. Unlike every other mangoes, Harumanis mangoes have a distinct taste. They have a slightly creamy and milky taste and a very strong and distinct aroma. If one to obtain the authentic or Grade A Harumanis, most likely have to go to the government farm (Jabatan Pertanian Perlis) at Sungai Batu Pahat. Recently, there is strategic collaboration between Jabatan Pertanian Perlis and UiTM Cawangan Pulau Pinang to elevate Harumanis mangoes prestige to the next level. One of the main strategy is to diversify Harumanis brand products to downstream products derived from other parts of the Harumanis plants to assist local farmers to increase their economic potentials. Herein, we propose an innovation called H-CUBE that derived from a Harumanis fruit extracts as the main ingredients. One of the major compound in this plant, called mangiferin, is believed to possesses medicinal and health benefits which deemed an attractive options to customers. The product will be launched by DYTM Raja Muda Perlis and will be commercialized this year. Distinct and unique aroma of the tea will please customers. This project will envisage to open more opportunities for the local farmers to enhance their income whilst promoting the brand name of Harumanis to higher level.